Strengthening Digital Financial Literacy and Perpetual Inventory Recording for BUMDes Tumang Managers in Cepogo, Boyolali - Rochmi Widayanti; Zianissa Amalia Putri; Ajeng Ayu (JARDIRA – Jurnal Pengabdian Digital dan Rekayasa Informatika, 2026)
Background: BUMDes Tumang Cepogo operates several business units, including waste-management services, financial services, logistics, and maggot cultivation. However, its managers still face limitations in financial literacy, inventory recording, and cost-based pricing, which affect the accuracy of financial information and business decision-making.Contribution: This community service program aimed to strengthen the digital financial literacy of BUMDes managers and introduce perpetual inventory recording through a Microsoft Excel-based template. The program also supported managers in identifying production-cost components and developing more accurate pricing decisions for maggot pellet products.Method: The program was conducted over four months in 2026 and involved five BUMDes managers. The activities included a needs assessment, development of a Microsoft Excel template, education on digital financial literacy and fraud prevention, training in recording purchase and sales transactions, simulations of stock cards and production-cost calculations, and evaluation through observation and practical assignments. Because no pre-test or post-test was administered, the outcomes were reported descriptively by comparing conditions before and after the mentoring program.Results: The participants were able to simulate transaction entries in Microsoft Excel, interpret changes in inventory balances, and prepare more structured production-cost estimates. The initial production cost of maggot pellets, calculated based on material and energy costs, was IDR 7,452/kg. After simulated allocations for labor, equipment depreciation, packaging, marketing, and transportation were included, the estimated full production cost increased to IDR 11,252/kg. At a selling price of IDR 12,000/kg, the estimated operating margin was only approximately 6.23%, indicating the need to reassess production scale, cost efficiency, and selling prices.Conclusion: The program improved participants’ ability to perform simulated digital financial recording, monitor inventory balances, and calculate production costs more systematically. However, the perpetual inventory method remained at the practice stage and had not yet been routinely implemented in daily operations. Further mentoring is therefore required to ensure consistent use of the template and to enable the resulting data to support BUMDes managerial decision-making